Histone/Serum Protein interactions, A cause of Pseudoimmunological reactions - Worthington, Robert Walter (Department of Biological Sciences, 2020)
Histones have been described by Murray (1964) as basic nuclear proteins which are at some time associated with DNA. Reviews on the biochemistry of histones have been written by Phillips (1962), Busch (1965 ), Butler, Johns and Phillips (1968), Hnilica (1967) and Bonner, Dabrnus, Fambrough, Huang, Marushige and Tuan (1968). These proteins are at present the subject of considerable interest because they are probably involved in the permanent repression of part of the genetic information of the DNA. If this is so, they must be basically involved in the control of cell differentiation.